(untitled) (Cardiovascular Journal, 2018)
Background: Neutrophil to lymphocyte ratio (NLR) has been proposed as a new prognostic marker in patients with chronic stable angina (CSA). NLR is a cheap, easily available, non-invasive and routinely done procedure to predict the severity of coronary artery disease. Methods: 110 patients with stable coronary artery disease were evaluated to calculate the NLR from January, 2016 to September, 2016. The patients were divided into two groups: Group I NLR>2.38 and group II NLRd”2.38. Coronary angiogram was done during index hospitalization. The severity of the coronary artery disease was assessed by vessel score and Gensini score and was compared between the groups. Results: NLR was significantly higher in the group of high vessel score and high Gensini score. We found significant weak association between NLR and vessel score (r=0.30, p=0.004) and a moderate positive correlation between NLR and Gensini score (r =0.65, P=0.001). With the increase of NLR, vessel score and Gensini score increases demonstrating more severe coronary artery disease. Univariate logistic regression analysis of variables of interest revealed that age, hypertension, dyslipidemia, serum creatinine, total WBC count and NLR were independent predictor of severe coronary artery disease with odds ratio (OR) being 1.88, 3.93, 5.01, 5.54, 4.05 and 5.70 respectively. In multivariate logistic regression analysis, after adjustment of factors NLR remain independent predictors of severe CSA (OR = 5.73; p = 0.002). Conclusion: Increased neutrophil to lymphocyte ratio is associated with angiographically severe coronary artery disease in chronic stable angina and this association is independent of conventional cardiovascular risk factors. Cardiovasc. j. 2018; 10(2): 164-170